Child nutritional status among births exceeding ideal family size in a high fertility population. Issue 4 (11th June 2018) - Costa, Megan E.; Trumble, Benjamin; Kaplan, Hillard; Gurven, Michael D.
Abstract: Ideal family size (IFS) is measured in social surveys to indicate unmet need for contraception and impending shifts in fertility behaviour. Whether exceeding IFS affects parental behaviour in ways that result in lower investments in child nutrition, well‐being, and educational attainment is not known. This study examines parental IFS and the association between exceeding stated ideals and child nutritional status in a high‐fertility, high‐mortality population in the Bolivian Amazon. Height‐for‐age z ‐scores, weight‐for‐age z ‐scores, weight‐for‐height z ‐scores, stunting, haemoglobin, and anaemia status in 638 children aged 0–5 years are predicted as a function of birth order in relation to parental IFS, adjusting for household characteristics and mother and child random effects. Children of birth orders above paternal IFS experience higher weight‐for‐age z ‐scores when living further away from the market town of San Borja, consistent with underlying motivations for higher IFS and lower human capital investment in children in more remote areas (β = .009, p = .027). Overall, we find no statistical evidence that birth orders in excess of parental ideals are associated with compromised child nutrition below age 2, a period of intensive breastfeeding in this population. Despite a vulnerability to nutritional deficiencies postweaning for children age 2–5, there was no association between birth order in excess of parental ideals and lower nutritional status. Further studies examining this association at various stages of the fertility transition will elucidate whether reported ideal or optimal family sizes are flexible as trade‐offs between quality and quantity of children shift during the transition to lower fertility.